The Role of the Agricultural Loan on the Development of Animal Sector in Al-Jabal Al-Akhdar Municipality - Khalifa, Rabiea K.; Shallof, Faisal M.; Tolba, Adly S. (Al-Mukhtar Journal of Sciences, 2008)
According to the state (government) trend to verify the base of the national economy and to create stabilized development in the economical sectors, the agricultural bank has been established to serve the agricultural sector in all regions. This bank is considered as one of the financial establishments that contribute to achieve the economical development by activating the main function of money in the society to realize the growth and development of the agriculture sector. IN AL Jabal AL-akhdhar Municipality- the subject of the field study. Moreover, it has been shown that the total agricultural loans granted by the bank in the different terms amounted (value) to approximately (136.25) million L.D during the period (1995-2005) where as the total of the recovered loans for the same period amounted (value) to approximately (72.38) million L.D .The percentage of the total the above recovered loans to the total granted loans was (53.1 %) for period. Where as the conclusions of the field study about the developmental effect of the agricultural loans on the various animal activities revealed that there is an increase in the number of the above mentioned animals and an increase in the income of the workers (farmers) after utilizing the loans amounted to (6570) L.D monthly (for all persons included in the field study) .This means: that' the average of the farmer/ s monthly income before gaining the loan was estimated to a value of (282) L.D, where as the same average of the concerned farmer after gaining the loan amounted (valued)to(345) L.D . The unavailabity of the sufficient liquidity of the bank resulted in the deficiency of the agricultural loans granted to the desired success of the agricultural activity especially after changing the exchange rate of the Libyan Dinar against the foreign currencies, which effects the real value of the granted loans, furthermore on the rising in the prices of factors of production requirements. All of the above reasons caused a difficulty in recovering the amounts loans granted to the farmers. Also the deduction of the interest directly from the granted loans before receiving it "decreases their value, then their desired role. A set of practical and scientific' recommendations have been suggested in this study to develop the financial policies and improve the performance of the credit establishments of agricultural bank within AL Jamahiriya such as to provide the financial support (Liquidity) for the agricultural bank to be able to cover all the required commitments of the 16ans (to meet the demand) , and to lessen the centralization. Also another suggestion is not to deduct the interest in advance from the loan, i.e in order to utilize the whole loans every installment of the loans which to be paid must include the loan amount (value) plus the interest. Also encouraging the role of the cooperative associations to avoid the individual guarantees problem. Also to simplify the procedures of getting the loans and to lessen the official routine to enable the small farmers to get the loans needed such as reduction of the loan costs especially the service charges